Identification of a New Cytotoxic T-Cell Epitope p675 of Human Telomerase Reverse Transcriptase - Huang, Guichun; Geng, Jian; Wang, Rui; Chen, Longbang (Cancer biotherapy & radiopharmaceuticals, 2012)
The identification of new tumor-associated antigens and epitopes is the prerequisite for cancer immunotherapy. The human telomerase catalytic subunit human telomerase reverse transcriptase (hTERT) is an attractive target for tumor therapy. The hTERT:540-548 peptide (p540, ILAKFLHWL) was previously identified as an HLA-A*0201-restricted T-cell epitope. However, other MHC-restricted epitopes in this antigen are urgently needed for an effective T-cell-based cancer treatment. The goal of this study was to identify other immunogenic peptides of hTERT restricted by HLA-A*0201 molecule, which accounts for about 15% of the Chinese population. Computer algorithms were used for epitope prediction, followed by analyzation on the plate of Discovery Studio 2.5. The candidate peptides were verified by T2-cell-binding assay, ELISPOT analysis, flow cytometry examination, and in vitro and in vivo tumor inhibition assay. Six peptides were predicted by computer algorithms. Of these peptides, p540 and p675 (LLGASVLGL) were identified with lower binding free energies than the other four peptides, binding to HLA-A*02 more strongly, and elicited stronger IFN-γ secretion of patients' peripheral blood mononuclear cells. The CTL clone against p675 elicited a significant cancer cell inhibition effect HLA-A*0201 restrictly. We identified p675 as a new HLA-A*0201-restricted T-cell epitope, and the CTL clone against it could suppress tumor growth effectively.